The developmental activities of skilled youth CONCACAF soccer players and the contribution of their development system - Andrew, M.; Baptiste, G. Z.; Reeves, M. J.; Roberts, S. J.; McRobert, A. P.; Ford, P. R. (International Journal of Sports Science & Coaching, 2022)
Small/er soccer nations rely strongly on developing youth athletes into experts in adulthood due to financial, logistical, and coach education constraints. One factor that contributes to this expertise is activities engaged in during childhood. Researchers have described these activities by focusing on larger, well-developed countries that often have larger participation rates and higher competition levels than their smaller counterparts. Therefore, to provide more specific information to support talent development in smaller soccer nations, a survey of the youth development system of a small soccer nation was conducted, alongside recording the developmental activities of skilled and less-skilled soccer players within this system. Key stakeholders (e.g., technical director) completed a youth development system survey. Skilled soccer players (n = 12) who were representing their country at U17 level and less-skilled players (n = 13) that had never played for their country completed a Participation History Questionnaire. Skilled players engaged in significantly higher amounts of individual practice in both childhood and early adolescence compared to less-skilled players. Survey data indicated that the greater amounts of individual practice for the skilled players stemmed from a lack of finances, playing facilities, and a formal coach education program. Results from this study may inform future practices and processes in the youth development systems of small/er soccer nations and their national associations.